A randomized controlled study comparing a vessel sealing system with the conventional technique in axillary lymph node dissection for primary breast cancer - Seki, Tomoko (Springerplus, 2016)
OBJECTIVE: This study aimed to compare the efficacy and safety of the newest bipolar vessel sealing system (BVSS; LigaSure™ Small Jaw) to that of conventional technique in axillary dissection. METHODS: Sixty-one patients with breast cancer were randomized to a conventional dissection surgical technique (CONV group; n = 30) by scalpel and monopolar cautery or that using a vessel sealing system (BVSS group; n = 31). RESULTS: There was a significant difference between both groups in the mean number of days until drain removal (6.4 ± 2.9 vs. 8.2 ± 3.8 days; P value = 0.033), and the mean total volume of drainage fluid (365.3 ± 242.2 vs. 625.1 ± 446.6 mL; P value = 0.009). The incidence of seroma was similar in both groups (43.3 vs. 37.9 %; P value = 0.673). There was no statistically significant difference in axillary dissection operating time (66 vs. 70 min; P value = 0.371), or the mean volume of blood loss (18.2 ± 31.1 vs. 20.6 ± 26.3 mL; P value = 0.663). CONCLUSIONS: Our results suggest that BVSS is a more effective device when compared to the conventional techniques in axillary dissection.